On the Influence of Reward on Action-Effect Binding - Muhle-Karbe, Paul S.; Krebs, Ruth M. (Frontiers in Psychology, 2012)
Ideomotor theory states that the formation of anticipatory representations about the perceptual consequences of an action (i.e. action-effect (A-E) binding) provides the functional basis of voluntary action control. A host of studies has demonstrated that A-E binding occurs fast and effortlessly, yet only little is known about cognitive and affective factors that influence this learning process. In the present study, we sought to test whether the motivational value of an action modulates the acquisition of A-E associations. To this end, we associated specific actions with monetary incentives during the acquisition of novel A-E mappings. In a subsequent test phase, the degree of binding was assessed by presenting the former effect stimuli as task-irrelevant response primes in a forced-choice response task in the absence of any reward. Binding, as indexed by response priming through the former action effects, was only found for reward-related A-E mappings. Moreover, the degree to which reward associations modulated the binding strength was predicted by individuals’ trait sensitivity to reward. These observations indicate that the association of actions and their immediate outcomes depends on the motivational value of the action during learning, as well as on the motivational disposition of the individual. On a larger scale, these findings also highlight the link between ideomotor theories and reinforcement-learning theories, providing an interesting perspective for future research on anticipatory regulation of behavior.